Market share in a post-entry game - Lee, C B; Fletcher, L R; Binner, J M; Murphy, W D (The Journal of the Operational Research Society, 2001)
This paper investigates the dynamics of market share within a contemporary, real life, entry deterrence situation in the provision of National Health Service (NHS) pathology services. The major conclusion is that the previous Government's initiatives did not succeed in promoting competition in markets where existing NHS providers were operating significantly more efficiently than their neighbours. Evidence suggests managers were influenced more by potential competition from a new private sector entrant than by actual competition among existing providers. The effect of a new entrant is modelled as a perturbation of a pre-existing stable equilibrium in a seeming oligopoly influenced by market forces subject to Government regulation. Economic analysis of the market share which a new entry might gain shows that, on the assumptions made and contrary to expectations, the likely impact of Government regulation of NHS prices would be an increase in price per test in most of the market. Nevertheless the policy objective of improving quality at value for money prices was achieved for the near-monopoly provider within our case study area.